Integrating Islamic Resources into Cognitive-Behavioural Therapy (Indian Journal of Psychology & Education, 2014)
Despite a substantial number of researches on depression, recognizing the list of symptoms within some categories, it is quite obvious that there are differences in how people express and experience depression especially on culture-related factors. Basically, most Western-developed therapeutic interventions like Cognitive Behaviour Therapy (CBT), Rational Emotive Behaviour Therapy (REBT) are based on the premise that human behaviour and emotions are basically the function of how an individual perceives and interprets his internal self and his environment. Moreover, there are growing concerns that therapeutic interventions should be adapted to suit cultural and religious orientation of the client because culture interplay with psychotherapy on three spheres which include, conception dilemma, approach to problem-solving, and treatment goal. Thus, this analytical paper examines the religio-cultural conception of depression among Muslims, and adopts the CBT based on Islamic concept of hope, meaning, and sense of gratitude to God. This is as a result of how Islamic teachings serve as an intervention towards relieving people with cognitive and emotional abyss. The purpose of this paper is to open a new window of integrating these positive and religious concepts into CBT which can help Muslim clients in particular, to learn and adopt other healthy ways of rational thinking and attaining inner meaning fulfillment in treating depression and other challenges in life.